System and Method to Define the Cost of Tax and Contribution Rates - Romero Molina, César Augusto; Colmenares Jácome, Ligia; Murillo Olarte, Andrea Catalina (DIXI, 2014)
This article arises from research entitled “System and Method to Defie the Cost of Tax and Contribution Rates”, carried out at the Bucaramanga campus of the Universidad Cooperativa de Colombia, Bucaramanga campus. Diffrent interpretations by the Constitutional Court on how the system and method for determining taxes and contributions rates operates and the insecurity generated by Article 338 of the Colombian Constitution that creates an interpretative vacuum regarding the question of who has the jurisdiction to establish these taxes and rates were analyzed. In order to give an answer to this question, a jurisprudential analysis from 1993 until 2012 is made and compared with the system and method used in the Spanish legislation